Analyzing the Perception of Generation Z on Using Podcasts to Improve English Listening Skills : A Qualitative Approach - Azzahro, Shania Zharfa Nur; Ahada, Ichi; Hermasgutiana, Istanti; Amarullah, A.K (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the perception of Generation Z regarding the use of podcasts as a learning medium to improve English listening skills. This study uses a descriptive qualitative approach with a case study design and involves students from the English Education Study Program at Mulawarman University who are part of Generation Z. Data were collected through a closed-ended questionnaire analyzed descriptively, and in-depth interviews analyzed using thematic analysis. The results indicate that most students have positive perceptions of podcast use, particularly regarding ease of access, increased learning motivation, vocabulary enrichment, and the effectiveness of podcasts in supporting listening skills. However, some students faced challenges such as limited internet connectivity and a lack of experience in regularly using podcasts. Based on the interviews, it was also found that engaging content types, such as viral issues, education, and general knowledge, were the main attractions for students. These findings indicate that podcasts are a potential and suitable learning medium for Generation Z, particularly in the context of English language learning in the digital age.